Adding the Neuromuscular Taping to Nerve Mobilization Interventions on the Hand Functional Abilities in Carpal Tunnel Syndrom - Ayu Permata; Renni Hidayati Zein; Brilian Dini MA. Iballa (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Carpal tunnel syndrome (CTS) is a collection of symptoms and signs of disease caused by the squeezing of the median nerve in the carpal tunnel in the wrist. This CTS condition is one of the most common types of neuropathy. This syndrome arises with symptoms of pain, numbness, and weakness in the hands due to compression of the median nerve. Carpal tunnel syndrome is a syndrome associated with repetitive motion and a fixed position for a long duration so it affects the blood supply to the hands and causes pain. This study aimed to determine the effectiveness of adding neuromuscular taping intervention to the nerve mobilization which was previously usually given to Hand Functional Ability in carpal tunnel syndrome. A case study with pre and post-test research a design that compares the Hand Functional Ability values before and after being measured with a measuring instrument Wrist hand Disability Index (WHDI) to provide additional Neuromuscular Taping intervention in conditions of carpal tunnel syndrome for 3 weeks. Analysis of differences scores with WHDI in the sample group with a significance value of 0.023 which shows < 0.05, which means there is an effect of giving additions Neuromuscular Taping Intervention in Nerve Mobilization noted changes in Hand Functional Ability levels in Carpal Tunnel Syndrome patients.